Great Zimbabwe - Chirikure, Shadreck, author.
1 online resource
Keywords: "Conditioned by local ways of knowing and doing, Great Zimbabwe develops a new interpretation of the famous World Heritage site of Great Zimbabwe. It combines archaeological knowledge, including recent material from the author's excavations, with native concepts and philosophies. Working from a large data set has made it possible, for the first time, to develop an archaeology of Great Zimbabwe that is informed by finds and observations from the entire site and wider landscape. In so doing, the book strongly contributes towards decolonizing African and world archaeology. Written in accessible manner, the book is aimed at undergraduate students, graduate students and practicing archaeologists both in Africa and across the globe. The book will also make contributions to the broader field such as African Studies, African History and World Archaeology through its emphasis on developing synergies between local ways of knowing and the archaeology"--